2019
DOI: 10.4152/pea.201902115
|View full text |Cite
|
Sign up to set email alerts
|

Study of Bitter Leaves Extract as Inhibitive Agent in HCl Medium for the Treatment of Mild Steel through Pickling

Abstract: Bitter leaves extract as inhibitive agent in HCl medium for the treatment of mild steel through pickling was studied. Thermometric, gravimetric and potentiodynamic polarization methods were employed in the corrosion inhibition study. The bitter leaves extract was analyzed using gas chromatography-mass spectrometer. The analysis of the extract revealed the presence of C6H8O (96 g/mole: 2,4-Hexadienal); C7H12 (96 g/mole: 3,4-Heptadiene; 1,3-Diethylallene) and C10H18O2 (170 g/mole: 2-Decenoic acid) as the predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The data obtained for the degree of surface coverage at various concentrations of the inhibitor were used to test Langmuir, Frumkin, Temkin and Flory–Huggins adsorption isotherms of equations (4) to (7), respectively (Li and Deng, 2012; Patel et al , 2013; Omotioma and Onukwuli, 2017; Onukwuli and Omotioma, 2019). The Gibb’s free energy of adsorption ( ΔG ads ) was calculated using equation (8): where C is the inhibitor concentration; K is the adsorption equilibrium constant; α is the lateral interaction term; “ a ” is the attractive parameter; θ is the degree of surface coverage; x is the size parameter; R is the gas constant; and T is the temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The data obtained for the degree of surface coverage at various concentrations of the inhibitor were used to test Langmuir, Frumkin, Temkin and Flory–Huggins adsorption isotherms of equations (4) to (7), respectively (Li and Deng, 2012; Patel et al , 2013; Omotioma and Onukwuli, 2017; Onukwuli and Omotioma, 2019). The Gibb’s free energy of adsorption ( ΔG ads ) was calculated using equation (8): where C is the inhibitor concentration; K is the adsorption equilibrium constant; α is the lateral interaction term; “ a ” is the attractive parameter; θ is the degree of surface coverage; x is the size parameter; R is the gas constant; and T is the temperature.…”
Section: Methodsmentioning
confidence: 99%
“…2 ; a) methyl nicotinate (C 7 H 7 NO 2 ), and b) pyridine-4-carbohydrazide (C 12 H 10 N 4 O 5 S). Methyl nicotinate and pyridine-4-carbohydrazide of the castor oil leaf contain heteroatoms of O, N and S. Presence of the heteroatoms, antioxidants as well as lengthy hydrocarbon chain revealed that the material is highly suitable for corrosion control [ 6 , 16 , 18 , 21 , 24 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Chemical constituent of the castor oil leaf extract was identified by gas chromatography-mass spectrometer (GCMS-QP2010 PLUS; SHIMADZU). The procedure used is similar to that of Onukwuli and Omotioma [ 21 ]. Features of gas chromatography (GC) and mass spectrometry (MS) were jointly applied to categorize different chemical constituents within the castor oil extract.…”
Section: Methodsmentioning
confidence: 99%
“…The chemical composition of the mango leaf extract are identified using instrumental analysis and gas chromatography-mass spectrophotometer (GCMS-QP2010 plus; Shimazu). The applied technique followed the technique used by previous research work [33]. Combined features of gas chromatography-mass spectrophotometer aided the categorization of the molecular constituents.…”
Section: Analysis Of the Chemical Composition Of Mango Leaf Extractmentioning
confidence: 99%